Research on Mechatronics Integration Modelling and Coupled Dynamic Characteristics in a Shearer Cutting Section Gearbox - Lu, Wenjia; Zhang, Yimin; Du, Zunling; Huang, Weibo (Archives of Mining Sciences, 2025)
The time-varying mesh stiffness (TVMS) and static transmission error (STE) are the main dynamic load excitation forms in the shearer cutting section gearbox (SCSG). The gearbox comprises two-stage planetary gear sets and multi-stage parallel gear sets. The structure of the multi-stage transmission and its rich internal dynamic excitation result in unique and complex dynamic behavior. In this paper, a coupled mechatronic integration dynamic model for SCSG and motor is developed, in which the multi-stage coupling excitation effects caused by gear mesh stiffness and static transmission error are fully simulated, thereby clarifying the interaction mechanism between the motor and transmission system. Based on the simulation model, the dynamic load characteristics of the SCSG are studied. The results show that load-sharing performance is improved with the increases of drum torque in the planetary gear sets (PGSs), which indicates that the load-sharing performance of the planetary gears can be effectively guaranteed in the process of increasing the coal mining rate. Through the combination of numerical simulation and experimental research, it is verified that the simulated signals are consistent with the experimental data for motor current. Meanwhile, relying on the proposed mechatronics model, extensive vibration information of the gearbox can be identified through the stator current signal. These results reference the vibration response analysis and signal monitoring of complex transmission systems.
Keywords: Longwall shearer; Planetary gear sets; Mechatronics model; Static transmission error; Dynamic characteristics; Load sharing performance